PENDEKATAN SUPERVISI COLLABORATIVE DALAM MEWUJUDKAN PEMBELAJARAN KREATIF - Solikah, Imroatus; Binti Maunah; Trisnantari, Hikmah Eva (Program Studi Manajemen Pendidikan Islam, 2024)
One of the external factors that results in low teacher professional competence is that the implementation of supervision by the school principal is carried out more in an assessing manner. Ideally, supervision itself is carried out in a collegial manner, not patronizing, and takes the form of partnership and mentoring, and is carried out through open and flexible discussion and brainstorming to help teachers reflect on their performance in carrying out their professional duties. In realizing creative learning, one of the approaches that can be used is an approach that prioritizes partnerships or co-workers between the principal as the academic supervisor and the teacher as the person being supervised, this approach is more of a companion through open and flexible discussion and brainstorming and has clear goals. It is clear that helping teachers develop into professionals through reflective activities is a collaborative supervision approach. This research uses the library research method, which focuses on collecting and analyzing data from written literature that is relevant to the results of the discussion including 1). understanding of a collaborative approach, 2). characteristics of a collaborative approach, 3). collaborative supervision approach process, 4). timing and goals of collaborative supervision approaches.